Clinical usefulness of telehealth: A literature review from the perspective of medical specializations - Octavius, Gilbert Sterling; Yen Hwei, Lie Rebecca (PT. Kalbe Farma Tbk., 2021)
Telehealth uses interactive technology and telecommunication to provide health care and share medical knowledge between the users. Information is transferred from one site to another electronically. Telehealth enables physicians to access the integrated electronic medical records in treating patients. Telehealth can be used for diagnostic, therapeutic, and preventive measures and self-education and self-monitoring of patients' health. Telehealth enables users to interact collaboratively with each other. Telehealth enables multiple medical specialties in providing health care services to a more significant population of patients. Telehealth is also a cost-effective method in providing health care services in both urban and rural areas. Telehealth may be an answer to problems associated with poverty, rural areas, and lack of medical personnel. The purpose of this article is to give insights into the use of telehealth in multiple medical specialties and its positive outcomes.Telehealth memanfaatkan teknologi dan telekomunikasi yang interaktif untuk memberikan akses pelayanan kesehatan dan berbagi pengetahuan seputar dunia medis bagi penggunanya. Informasi ditransfer dari satu situs ke situs lain secara elektronik. Telehealth memungkinkan dokter untuk mengakses catatan medis elektronik terintegrasi saat merawat pasien. Telehealth dapat digunakan untuk tindakan diagnostik, terapeutik, pencegahan serta pendidikan dan pemantauan mandiri bagi para pasien. Telehealth memungkinkan pengguna untuk berinteraksi secara kolaboratif satu sama lain. Telehealth juga memungkinkan beberapa spesialisasi medis dalam memberikan layanan perawatan kesehatan kepada populasi pasien yang lebih banyak. Telehealth juga merupakan metode yang hemat biaya dalam menyediakan layanan perawatan kesehatan di daerah perkotaan dan pedesaan. Telehealth dapat menjadi jawaban atas masalah yang terkait dengan kemiskinan, daerah pedesaan, dan kurangnya tenaga medis. Tujuan artikel ini adalah untuk memberikan wawasan tentang penggunaan telehealth dalam berbagai spesialisasi medis dan hasil positifnya.